Dopamine Triggers CTCF-Dependent Morphological and Genomic Remodeling of Astrocytes - Galloway, Ashley; Adeluyi, Adewale; O'Donovan, Bernadette; Fisher, Miranda L.; Rao, Chintada Nageswara; Critchfield, Peyton; Sajish, Mathew; Turner, Jill R.; Ortinski, Pavel I. (The Journal of neuroscience, 2018)
Dopamine is critical for processing of reward and etiology of drug addiction. Astrocytes throughout the brain express dopamine receptors, but consequences of astrocytic dopamine receptor signaling are not well established. We found that extracellular dopamine triggered rapid concentration-dependent stellation of astrocytic processes that was not a result of dopamine oxidation but instead relied on both cAMP-dependent and cAMP-independent dopamine receptor signaling. This was accompanied by reduced duration and increased frequency of astrocytic Ca 2+ transients, but little effect on astrocytic voltage-gated potassium channel currents. To isolate possible mechanisms underlying these structural and functional changes, we used whole-genome RNA sequencing and found prominent dopamine-induced enrichment of genes containing the CCCTC-binding factor (CTCF) motif, suggesting involvement of chromatin restructuring in the nucleus. CTCF binding to promoter sites bidirectionally regulates gene transcription and depends on activation of poly-ADP-ribose polymerase 1 (PARP1). Accordingly, antagonism of PARP1 occluded dopamine-induced changes, whereas a PARP1 agonist facilitated dopamine-induced changes on its own. These results indicate that astrocyte response to elevated dopamine involves PARP1-mediated CTCF genomic restructuring and concerted expression of gene networks. Our findings propose epigenetic regulation of chromatin landscape as a critical factor in the rapid astrocyte response to dopamine. SIGNIFICANCE STATEMENT Although dopamine is widely recognized for its role in modulating neuronal responses both in healthy and disease states, little is known about dopamine effects at non-neuronal cells in the brain. To address this gap, we performed whole-genome sequencing of astrocytes exposed to elevated extracellular dopamine and combined it with evaluation of effects on astrocyte morphology and function. We demonstrate a temporally dynamic pattern of genomic plasticity that triggers pronounced changes in astrocyte morphology and function. We further show that this plasticity depends on activation of genes sensitive to DNA-binding protein CTCF. Our results propose that a broad pattern of astrocyte responses to dopamine specifically relies on CTCF-dependent gene networks.